Moral Value and Character Building Education in Film : Denias, Senandung di Atas Awan - Yenita Br. Sembiring; Veronika Anastasya Br Purba; Tiur Maulina Panjaitan; Lampita Deniska Sitorus; Artha Priscilla Sijabat (Peneliti.net, 2021)
This study entitled MORAL VALUE AND CHARACTER BUILDING EDUCATION IN FILM: DENIAS, SENANDUNG DI AWAN, aims to determine the moral values and character-building education contained in the film Denias, Senandung di Atas Awan. This research was conducted using qualitative methods. The data collection instrument is documentation. The analysis technique in this research is by using the qualitative descriptive technique. Qualitative descriptive methods are described, provide, analyzed, and interpret. After analyzing folklore, the researcher found several moral lessons and character-building education such as; believe in God's power, being dutiful to parents, teach to a child to be excited, polite to older people, having a high obsession, unwavering, persistent spirit, sharing, and caring.